Assessing Food Safety Knowledge and Awareness Among Hospital Food Handlers in Qatar: A Cross‐Sectional Study - Nahlah AlMesbah (21393002) (2025)
In large‐scale cooking environments, such as hospital catering, the risk of food contamination due to improper handling escalates with numerous personnel’s involvement. Given the critical nature of hospital settings, ensuring stringent adherence to food safety protocols is imperative to prevent adverse health outcomes. This study aims to evaluate food safety knowledge and awareness concerning safe food handling practices among Qatar hospital catering staff, enhancing patient safety and improving healthcare quality. A cross‐sectional survey utilizing a validated self‐administered questionnaire was conducted among food handlers employed by Hamad Medical Corporation between November 13 and December 7, 2023. The questionnaire was distributed across various hospital facilities. The study involved 366 participants, 60.9% exhibiting good knowledge, 30.1% satisfactory, and 9% lacking adequate food safety knowledge. Similarly, 95.9% of participants exhibited good, 3% demonstrated satisfactory, and 1.1% displayed inadequate awareness regarding safe food handling practices. Significant disparities in total knowledge scores were observed across marital status categories (p = 0.043) and job positions (p = 0.002). Furthermore, variations in total awareness scores about safe food handling practices were noted among different categories of years of experience (p = 0.009) and job positions (p = 0.016). Although overall knowledge and awareness among hospital catering staff in Qatar were commendably high, periodic refresher courses are recommended to sustain adherence to best practices. Additionally, continuous oversight and qualitative research to observe actual food handling behaviours are crucial for maintaining optimal food safety standards, complementing self‐reported practices. Other Information Published in: International Journal of Food Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1155/ijfo/5450277